Optimization of Task Allocation for Collaborative Brain–Computer Interface Based on Motor Imagery - Gu, Bin; Xu, Minpeng; Xu, Lichao; Chen, Long; Ke, Yufeng; Wang, Kun; Tang, Jiabei; Ming, Dong (Frontiers in Neuroscience, 2021)
Objective. Collaborative Brain-Computer Interfaces (cBCIs) can make the BCI output more credible by jointly decoding concurrent brain signals from multiple collaborators. Current cBCI systems usually require all collaborators to execute the same mental tasks (common-work strategy). However, it is still unclear whether the system performance will be improved by assigning different tasks to collaborators (division-of-work strategy) while keeping the total tasks unchanged. Therefore, we tried task allocation scheme of division-of-work and compared the corresponding classification accuracies with the common-work strategy’s. Approach. This study developed an electroencephalograph (EEG)-based cBCI which had six instructions related to six different motor imagery tasks (MI-cBCI), respectively. For the common-work strategy, all 5 subjects as a group had the same whole instruction set and they were required to conduct a same instruction at a time. For the division-of-work strategy, every subject’s instruction set was a subset of the whole one and different from each other. But their union set was equal to the whole set. Based on the number of instructions in a subset, we divided the division-of-work strategy into four types, called “2 Tasks” … “5 Tasks”. To verify the effectiveness of these strategies, we employed EEG data collected from 19 subjects who independently performed 6 types of MI tasks to conduct the pseudo-online classification of MI-cBCI. Main results. Taking the number of tasks performed by one collaborator as the horizontal axis (2 to 6), the classification accuracy curve of MI-cBCI was mountain-like. The curve reached its peak at “4 Tasks” which means each subset contained 4 instructions. It outperformed the common-work strategy (“6 Tasks”) in classification accuracy (72.29±4.43% vs 58.53±4.36%). Significance. The results demonstrate that our proposed task allocation strategy effectively enhanced the cBCI classification performance and reduced the individual workload.